The Factors Affecting the Decision to Use the Fitness Center in Bangsean Chonburi - Anwong, Prapawadee; Lertbuddhalak, Saranya; Khamloy, Wilailuk (KKBS Journal of Business Administration and Accountancy, 2020)
This research aims to study the factors influencing the decision to use the fitness center in Bangsaen, Muang District, Chonburi. This is mixed-methods research. First, in quantitative research, the samples were 361 fitness-center members. Data was collected using a questionnaire. Second, qualitative research uses in-depth interviews with the 5 entrepreneurs or managers of the fitness business center in Bangsaen, Muang District, Chon Buri. It was found that the composition of the fitness center concerning gym amenities and advertising & PR influenced the decision making to sign up for fitness-center membership a statistical significance level of 0.01. The qualitative analysis of the marketing management approach for the fitness-center business showed that the entrepreneurs focused on the components of the fitness center in 10 areas, i.e.location, atmosphere and environment, price and promotion, expertise, cleanliness, exercise equipment, workout program, facility, results and expectations, and advertising & PR. The result was in line with the quantitative finding that the major factors affecting the decision making to sign up for fitness-center membership were advertising & PR and gym amenities.